Judiciaries within Europe : a comparative review / John Bell. - Bell, John, 1953- (Cambridge studies in international and comparative law (Cambridge, England : 1996) ;, 2006)
An in-depth study, originally published in 2006, of the careers and roles of judges in France, Germany, Spain, Sweden and England, this book is based on original language materials and investigations of judges and judicial institutions in each country. On the basis of these detailed case studies, the book suggests factors that shape the character of the judiciary in different countries, focusing on issues such as women's careers and the relationship between judicial careers and politics. Bell's investigations offer lessons on issues which the English judiciary was having to confront in the period of reform at the time of this book's publication.